Kemiskinan di Wilayah Kaya Sumber Daya: Analisis Kualitas SDM dan Kesempatan Kerja, Kabupaten Mimika, Papua Tengah - Maya Khoirotunnisa; Himayatin Nikmah (Jurnal Riset Multidisiplin Edukasi, 2026)
Mimika Regency, Central Papua Province, is one of the regions in Indonesia rich in natural resources, particularly copper and gold mines. Exploitation of these resources contributes significantly to the national economy, but ironically, this has not been accompanied by an increase in the welfare of the community equally. The poverty rate in Mimika remains quite high, although it shows a downward trend (around 13.7% in March 2025 according to BPS)—higher than the national average and remains a major development issue in the region. This phenomenon is influenced by the quality of human resources and limited inclusive employment opportunities for local communities. Low human resource capacity, limited education and vocational training, and the dominance of the extractive sector hinder broader workforce absorption. Furthermore, unequal access to public facilities such as clean water, healthcare, and education worsens socioeconomic conditions. Various news sources indicate that natural resources have not been able to address the structural problems of poverty due to weak benefit distribution systems, corruption, and a lack of economic diversification. This analysis uses recent news studies and statistical data to evaluate the relationship between natural resources, human resource quality, and employment opportunities in Mimika. Findings indicate that without improving human resource quality and inclusive employment opportunities, poverty will remain a challenge despite abundant natural resources. This study concludes that policies are needed to focus on human development, economic diversification, improved job training, and equitable distribution of natural resource benefits to local communities.